2020
DOI: 10.1021/acsabm.9b00911
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Coating Method for Amine-Rich Surfaces using Poly(ethylene glycol) Diacrylate Applied to Bioprosthetic Valve Tissue Models

Abstract: Bioprosthetic heart valve implants are beset by calcification and failure due to the interactions between the body and the transplant. Hydrogels can be used as biological blank slates that may help to shield implants from these interactions; however, traditional light-based hydrogel polymerization is impeded by tissue opacity and topography. Therefore, new methods must be created to bind hydrogel to implant tissues. To address these complications, a two-step surface-coating method for bioprosthetic valves was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
(67 reference statements)
0
11
1
Order By: Relevance
“…This method produced a robust, substantial coating along the length of the valve specimen. This result was an improvement over our previous report in which a continuous coating was only achievable on a model system and showed patchy and limited deposition on tissue . The minor coating discontinuities found in this study were likely due to sample handling when creating cross sections.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…This method produced a robust, substantial coating along the length of the valve specimen. This result was an improvement over our previous report in which a continuous coating was only achievable on a model system and showed patchy and limited deposition on tissue . The minor coating discontinuities found in this study were likely due to sample handling when creating cross sections.…”
Section: Discussioncontrasting
confidence: 45%
“…Assessment of the no PEG-coated control samples verified that this reduction was because of the PEG and not the coating process. These results were anticipated as PEG-based hydrogels have been previously shown to be protein-repellent and are often used to prevent adsorption. , Our previous research analyzing a PEGDA coating on a tissue model system also showed significant protein reduction after the coating was applied …”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Tissue engineering studies must show evidence that materials are able to both match the non-pathological mechanical behavior of the diseased or damaged tissue they were designed to replace [2] and withstand the mechanical forces they will be subjected to under physiological conditions [3]. Similar characterization must be performed on any graft [4], stent [5], coating [6], or similar in vivo device [7][8][9] supporting normal physiological processes to ensure proper function and longevity. Mechanical testing is performed on a wide variety of artificial [10], bio-inspired [11], or completely biological [12] materials.…”
Section: Introductionmentioning
confidence: 99%